2012
DOI: 10.1142/s0218216511010103
|View full text |Cite
|
Sign up to set email alerts
|

THE KHOVANOV HOMOLOGY OF (p, -p, q) PRETZEL KNOTS

Abstract: In this paper, we compute the Khovanov homology over Q for (p, −p, q) pretzel knots for 3 ≤ p ≤ 15, p odd, and arbitrarily large q. We provide a conjecture for the general form of the Khovanov homology of (p, −p, q) pretzel knots. These computations reveal that these knots have thin Khovanov homology (over Q or Z). Because Greene has shown that these knots are not quasi-alternating, this provides an infinite class of non-quasi-alternating knots with thin Khovanov homology.Since α, β, and γ preserve quantum gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
(13 reference statements)
1
12
0
Order By: Relevance
“…Remark 5.5. We expect that L(K n ) = 0 for all n. Indeed, each K n has thin Khovanov homology [41]. Hence, by a well-known conjecture (cf.…”
Section: Examples and Nonreversible Lagrangian Concordancesmentioning
confidence: 91%
“…Remark 5.5. We expect that L(K n ) = 0 for all n. Indeed, each K n has thin Khovanov homology [41]. Hence, by a well-known conjecture (cf.…”
Section: Examples and Nonreversible Lagrangian Concordancesmentioning
confidence: 91%
“…Starkston has conjectured [18] and Qazaqzeh [17] has shown that the Khovanov homology of P (−p, q, r) is thin if p = min{q, r}, and Manion [13] has proved that it is not thin if 2 ≤ p < min{q, r}.…”
Section: 2mentioning
confidence: 99%
“…The next step was the explicit computation of unreduced Khovanov polynomials for several infinite series of non-quasi-alternating genus 2 pretzel links [34][35][36]. All these polynomials proved to be homologically thin, and thus similar to the polynomials of the alternating links.…”
Section: Khovanov Polynomials For Genus 2 Prezel Knotsmentioning
confidence: 99%